ANALISIS DUGAAN AKTIVITAS ILLEGAL FISHING OLEH KAPAL IKAN BERBENDERA RUSIA DI LAUT ARAFURA: TINJAUAN YURIDIS DAN STRATEGI KEAMANAN MARITIM INDONESIA - I Gede Gohan Adiputra; Fahreza Putri; Maitsaa Bhanucetta; Maurora Sholehaliza B. P.; Lintang Elok Azaly; Caren Gilbert Edward Mintalangi (Journal of International Relations Diponegoro, 2025)
The observation of illegal fishing activities by Russian ships in the Arafura Sea threatens Indonesia's maritime sovereignty as well as the preservation of Indonesia's marine ecosystem and economy. This research uses qualitative methods and case studies to analyze legal aspects and maritime security strategies applied by Indonesia. Research results show that although Indonesia has a strong legal basis such as Law number 45 of 2009 and Presidential Decree number 115 of 2015, its implementation is faced with obstacles such as limited supervision fleet and lack of coordination between institutions. To deal with this situation, the strategy used is to strengthen technology supervision, organize closer international cooperation, and empower local fishermen. This strategy is expected to maintain maritime sovereignty, protect marine resources, and support ecosystem sustainability in the Arafura Sea.